Learning outcomes in validation and credit systems - Bjornavold, Jens [Verfasser]; Le Mouillour, Isabelle [Verfasser] (My University, 2010)
"Instruments and arrangements supporting transfer and accumulation of learning outcomes, such as validation and credit systems, form an important part of European and national lifelong learning strategies. Debate has largely focused on separate initiatives and failed to address how these may interact and could create synergies. A starting point for the analysis is the continuing shift to learning outcomes taking place in most European education and training systems. This is exemplified and supported by the introduction of comprehensive qualifications European (EQF) and national (NQF) frameworks, by increased use of validation of non-formal and informal learning and by the development of credit systems in education and training (ECVET). The article addresses the possible relationships between validation and credit systems, how they may contribute to lifelong learning by aiding recognition of all forms of learning outcomes, irrespective of their origin in formal, non-formal and informal settings. The review on existing patterns and future developments ends by identifying several issues which would need further research and policy-development." (Autorenreferat, BIBB-Doku)
Keywords: I 1.2 Anrechnung im Ausland erworbener Leistungen & Abschlüsse; S 2.3 Berufsbildungspolitik; I 2.2 Europa; EU-Bildungspolitik; Anrechnung von Bildungsleistungen; Europäisches Leistungspunktesystem; Informelles Lernen; Lernergebnisorientierung; Europäischer Qualifikationsrahmen